(untitled) (Scientific journal of the Fergana State University, 2023)
This article systematically analyzes the formation of regional TV channels in our country and their impact on socio-political processes. The process of development of local television in our republic and its role in the life of citizens are studied according to the principle of historicity. The article uses such methods of scientific analysis as analysis and synthesis, periodicity, historical and descriptive approach. Approaches and methods recognized in history, historical literature, primary sources, such as official websites and publications of communication companies, articles published in newspapers, magazines, and collections were also used.